Students’ Analogical Reasoning in Solving Number Pattern Problems - Intan Juniarmi; Rohati Rohati; Duano Sapta Nusantara (MASI Mandiri Edukasi, 2025)
This study aimed to analyze students’ answers in solving number pattern problems in terms of analogical reasoning ability. Six seventh-grade students with varying academic levels participated in the study. Data were collected through written tests and semi-structured interviews, then analyzed using the analogical reasoning framework, which includes four indicators: encoding, inferring, mapping, and applying. The results showed that the total scores of the six participants ranged from 18 to 30. Student 1 obtained the lowest score (18), indicating weaknesses particularly in applying pattern rules to determine the required terms correctly. In contrast, Students 3, 4, and 5 achieved the maximum score of 30, demonstrating consistency in recognizing pattern rules, mapping structural similarities, and applying their reasoning accurately across tasks. The average total score was 27.5, suggesting that most students demonstrated relatively strong analogical reasoning skills, although some individuals still experienced difficulty in the applying stage, which demands higher precision and conceptual understanding. The study contributes to understanding how analogical reasoning influences students’ mathematical problem-solving and offers pedagogical insights for enhancing instruction of non-routine tasks through reasoning-based learning strategies.